2013
DOI: 10.1098/rstb.2012.0484
|View full text |Cite
|
Sign up to set email alerts
|

Capital and income breeding traits differentiate trophic match–mismatch dynamics in large herbivores

Abstract: For some species, climate change has altered environmental conditions away from those in which life-history strategies evolved. In such cases, if adaptation does not keep pace with these changes, existing life-history strategies may become maladaptive and lead to population declines. We use life-history theory, with a specific emphasis on breeding strategies, in the context of the trophic match–mismatch framework to form generalizable hypotheses about population-level consumer responses to climate-driven pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 62 publications
1
101
1
Order By: Relevance
“…However, this same increase in temperature will also likely increase insect harassment; provide opportunity for predators, potential competitor species, parasites, and diseases that have historically been restricted to more southerly ranges to expand northward; and alter plant community composition to be dominated by potentially less nutritious species (Sharma et al 2009;Witter et al 2012a;Kutz et al 2013;Thompson and Barboza 2014;Simard et al 2016). Additionally, all Rangifer populations may not respond positively to the advancement of spring (Post and Forchhammer 2008;Kerby and Post 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, this same increase in temperature will also likely increase insect harassment; provide opportunity for predators, potential competitor species, parasites, and diseases that have historically been restricted to more southerly ranges to expand northward; and alter plant community composition to be dominated by potentially less nutritious species (Sharma et al 2009;Witter et al 2012a;Kutz et al 2013;Thompson and Barboza 2014;Simard et al 2016). Additionally, all Rangifer populations may not respond positively to the advancement of spring (Post and Forchhammer 2008;Kerby and Post 2013).…”
Section: Discussionmentioning
confidence: 99%
“…plants, herbivores and predators). The last point is important because, for endotherms inhabiting the tundra, it has been suggested that the most severe impact of climate warming may be indirect, through alterations in trophic interactions such as change in food availability, predation pressure, apparition of new competitors or mismatch between trophic levels [25][26][27]. Therefore, a food web approach is essential in order to fully understand the impact of climate warming on individual species [28].…”
Section: Introductionmentioning
confidence: 99%
“…Several income breeding Antarctic bird and mammal species, which experience frequent and unpredictable fluctuations in prey abundance due to extreme climatic events that trigger krill declines and associated trophic cascades, cope with environmental change by either deferring reproduction to the next year or reproducing as normal but incurring the penalty of reduced survival and fitness (Forcada et al 2008). Similarly, income breeding caribou in Greenland were constrained in their ability to reproduce with fluctuations in resource abundance, but the co-occurring, capital-breeding muskoxen, experienced no decline in reproduction under the same environmental changes, as they relied upon energy reserves garnered over the previous year (Kerby and Post 2013). Recent study with an income breeding lycaenid butterfly (see Hill and Pierce 1989;Fischer and Fiedler 2001 for income feeding effects on physiologically similar taxa), suggest a single, resource-matching strategy for oviposition, regardless of burn history and an increase in progeny survival associated with colonizing recently burned habitat (Warchola et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Strict capital breeding species do not require spatial and temporal overlap of concurrent energy resources for reproduction, so selection should favor the evolution of alternative reproductive strategies to cope with environmental change as strict capital breeding species are incapable of buffering against poor reproductive choices with supplemental income (Bonnet et al 1998;Stephens et al 2009). However, empirical study of the reproductive responses by strict capital breeding species to environmental change is rare (Stephens et al 2009;Kerby and Post 2013), leaving this aspect of life history evolution largely hypothetical.…”
Section: Introductionmentioning
confidence: 99%